TINJAUAN YURIDIS KECAKAPAN BERTINDAK PARA PIHAK DALAM PERJANJIAN UTANG-PIUTANG (STUDI PERJANJIAN PADA ERICKO CHANIAGO DENGAN PT. BCA FINANCE DAN CV. TRIJAYA MAKMUR SEJAHTERA) - Bloude, Bastian; Indiraharti, Novina Sri (Tribuere, 2023)
In an agreement, must pay attention to the provisions of Article 1320 of the Civil Code, one of the conditions is the acting skills of the parties when making the agreement. In this case, there was an agreement which, at the time it was made, one of the parties was not competent in carrying out legal acts, which conducted by Ericko Chaniago with PT BCA Finance and CV Trijaya Makmur Sejahtera. The problem in this research is: how is a person's maturity regulated as a condition for the validity of their ability to act in making an agreement? and whether the agreement made between Ericko Chaniago and PT BCA Finance and CV Trijaya Makmur Sejahtera meets the requirements for the validity of the agreement, especially regarding the element of the parties' acting skills? The method used in this research is a normative juridical method, using secondary data as the main data, in the form of primary legal materials, namely using statutory regulations and secondary materials in the form of literature, processing is carried out qualitatively and conclusions are drawn deductively. The results of this research concluded, that a person's maturity in Indonesian laws and regulations varies, in the Civil Code, a person's maturity is 21 (twenty one) years, but Indonesian law recognizes that a person's maturity is 18 (eighteen) years, one of which is as intended in the Notary Position Law, and it was found that the agreement made by Ericko Chaniago with PT BCA Finance did not meet the elements of acting skill of the parties, because Ericko Chaniago was still under 21 (twenty one) years of age, while for the agreement between Ericko Chaniago and CV Trijaya Makmur Sejahtera had fulfilled the requirements for the parties' acting skills, but it was found that there was a violation of other conditions, namely the existence of unlawful causes in the agreement.